The role of CO2 detachment in fungal bioluminescence: thermally vs. excited state induced pathways. Issue 46 (19th November 2020) - Garcia-Iriepa, Cristina; Marazzi, Marco; Navizet, Isabelle
Abstract : The fungal emission mechanism elucidated by computational chemistry: thermal CO2 release followed by peroxide breaking and excited state population. Abstract : Different fungi lineages are known to emit light on Earth, mainly in tropical climates. Although the preparation of bioluminescent cell-free extracts allowed one to characterize the enzymatic requirements, the molecular mechanism underlying luminescence is still largely unknown and is based on the experimental putative assumption that a high-energy intermediate should be formed by reaction with O2 and formation of an endoperoxide. Here, we aim at determining, through state-of-the-art multiconfigurational quantum chemistry, the full mechanistic landscape leading from the endoperoxide to the emitting species, envisaging different possible pathways and proposing their viability. Especially, thermal CO2 detachment followed by excited-state peroxide opening (thermal-chemiluminescence) can compete with a parallel pathway, i.e., first excited-state endoperoxide opening, followed by CO2 detachment on the same excited-state (excited state-chemiluminescence). Clear differences in the energy supplies, as well as the possibility to directly populate the emitting species from the intersection seam between ground and excited states, land credence to a kinetically efficient thermal-chemiluminescent pathway, establishing for the first time a detailed description of fungal bioluminescence.